(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the importance of modern marketing and management principles in the process of sustainable economic development in the Republic of Uzbekistan, their interrelationships and practical application possibilities. It also highlights effective methods of ensuring economic stability based on innovative approaches, digital technologies and the principles of social responsibility.